Expression of MMP-2 as Biological Markers of Invasion Potential in Mucoepidermoid Carcinoma of the Oral and Maxillofacial Region (Immunohistochemical Study ) - Taher, Mustafa G; Abdullah , Bashar H; Al-Khuri , Luay E (Diyala Journal of Medicine, 2019)
Background: Mucoepidermoid carcinoma (MEC) is a malignant epithelial neoplasm characterized by the proliferation of epidermis, mucous, and intermediate cells in various proportions, it represents up to 10% of all major salivary glands tumors and 15% to 23% of minor glands. It exhibits varying degrees of differentiation and histologic grade as well as widely diverse biologic behavior. Its grading system is based on different histological components seen on hematoxylin and eosin slide which is still a controversial issue. This study evaluates the immunohistochemical expression of MMP-2 antibodies as markers of local invasion of MEC to be correlated with the tumor grade and stage. Aim of the study: Immunohistochemical evaluation MMP-2 as a biological markers of local invasion in oral and maxillofacial salivary MEC in relation to grading and staging of MEC. Materials and Methods: The study involved 22 salivary gland MEC tissue samples for the period from 1972 to 2010. Age, sex, site, stage and histologic grades were recognized. The samples were immunohistochemically stained with monoclonal antibodies to matrix metalloproteinase-2 (MMP-2). Results: The sample comprised 14 males and 8 females in (1.75:1) ratio. The age range of the patients was between 19 and 65 years with a mean of (45.9±10.53). The stage of MEC had a significant relationship with Brandwein grading system (P=0.039). Concerning the site and sex distribution, neither site nor sex had a significant statistical relationship with Brandwein grading system (p> 0.05). The mean of matrixmetaloprotenase-2 expressed by MMP-2 immunomarker was (41.7±23.13) with no significant relation to tumor grade and stage . Regarding the predominant cells, no significant relations were found neither with the grade nor the stage of study samples. Conclusions: In all samples, matrixmetalloproteinase-2 had a non significant relationship with tumor grade and stage. No correlation was found between the histological grading of MEC and its biological behavior concerning invasion potential.